Plankton Diversity as a Natural Food Source for Milkfish (Chanos chanos) in Traditional Ponds of Pasuruan City, East Java - Ike Listya Anggraeni; Hartati Kartikaningsih; Agung Pramana Warih Marhendra (Jurnal Penelitian Pendidikan IPA, 2025)
Traditional ponds in Pasuruan City are dominated by milkfish (Chanos chanos). Milkfish take food from the top layer of the seabed in the form of phytoplankton and zooplankton. This study aims to determine the abundance, diversity and dominance of plankton and water quality in traditional milkfish ponds in Pasuruan City. Sampling locations were selected based on the distance of the pond from the sea. Station 1 (near the sea), station 2 (1–3 km from the sea), and station 3 (furthest from the sea). The results showed the availability of natural food for milkfish in the form of phytoplankton and zooplankton. Phytoplankton was found more than zooplankton. The most common phytoplankton division was Bacillariophyta and the least was Euglenozoa with diversity index ranging from 1.64–1.82 and dominance index ranging from 0.24–0.31. The most common zooplankton phylum is Arthropoda and the least is Molluscs with diversity index ranging from 0–1.83 and dominance index ranging from 0.21–1.00. The measurement results of pond water quality parameters such as pH (8.51–9.02), temperature (30.1–32.5°C), brightness (25.5–29.6 cm), DO (3.7–5.7 ppm) and salinity (32.5–33.7 ppt) are still in accordance with the optimal standards of milkfish farming.